Home » Make t the subject of formula S = ut + (frac{1}{2} at^2)

Make t the subject of formula S = ut + (frac{1}{2} at^2)

Make t the subject of formula S = ut + (frac{1}{2} at^2)
  • A.
    (frac{1}{a}) (-u + (sqrt{U^2 – 2as}))
  • B.
    (frac{1}{a}) {u (pm) (U2 – 2as)}
  • C.
    (frac{1}{a}) {u (pm) (sqrt{2as})}
  • D.
    (frac{1}{a}) {-u + (sqrt{( 2as)})}
Correct Answer: Option A
Explanation

Given S = ut + (frac{1}{2} at^2)
S = ut + (frac{1}{2} at^2)
∴ 2S = 2ut + at2
= at2 + 2ut – 2s = 0
t = (frac{-2u pm 4u^2 + 2as}{2a})
= -2u (pi) (frac{sqrt{u^2 4u^2 + 2as}}{2a})
= (frac{1}{a}) (-u + (sqrt{U^2 – 2as}))

Related:  Which of the following is a factor of rs + tr - pt - ps?